Serum Lipid Profile as an Indicator of Severity of Liver Cirrhosis - Mujahid, Muhammad Mamoon; Fazal, Imran; Siddiqi, Umair Ahmad; Tahir, Fraz; Haider, Ehtisham; Asghar, Asma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To look for the relationship of deranged lipid profile with severity of liver cirrhosis along with other sociodemographic factors at Pak Emirates Military Hospital Rawalpindi.Study Design: Cross sectional study.Setting and Duration of Study: Gastroenterology department, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2018 to Feb 2019.Methodology: Eighty patients suffering from cirrhosis admitted in the medical ward or reporting in outpatient department of Pak Emirates Military Hospital were included in this study. Diagnosis of cirrhotic liver was made based on clinical findings and relevant investigations and severity of cirrhosis was established by using the Model for end stage liver disease (MELD) score. Total cholesterol, LDL cholesterol and HDL cholesterol and triglyceride levels were correlated with the severity of cirrhosis in the target population along with other factors.Results: Out of 82 patients included in the final analysis 49 (59.7%) were male and 33 (40.3%) were female. Most of the patients presented with the chronic liver disease secondary to the hepatitis C virus (HCV). 45 (54.8%) had MELD score >10 while 37 (45.2%) had MELD score